ELASTISITAS PRODUKSI BUDIDAYA RUMPUT LAUT DI KELURAHAN PANTAI AMAL KECAMATAN TARAKAN TIMUR - Sonu, Karolus; Daengs, Achmad (JEB17 : Jurnal Ekonomi dan Bisnis, 2020)
Indonesia as an archipelago which has waters area bigger than the mainland. Indonesia seawaters resources is diverse and shall be managed efficiently to improving the Indonesian welfare. The objective of this study to examine the production elasticity of seaweed culvation in Amal Beach, East Tarakan subdistrict. Data required in this analysis is total cost of the production that is labor cost, seed purchase, seed, and many more which categorized as work capital during the production process until the harvest time in specific period. The number of labor usage (person) of each farmer for the production process until harvest time in specific period. Data result of the seaweed production in specific period harvest time. The result show that elasticity of labor and seed concurrently on production also has increasing Return of Scale that is : IRTS = ? + ? = 0,95 + 0,11 = 1,06 means that every seed addition and labor concurrently as high as one unit then the production result increase only around 1.06 unit. The proportion of production result add bigger than production factor add. Value of X1 as 112,131 that means seed cost being incurred be suggested as Rp. 112,131 per m2, while value of X2 as 0,067 that equate labor cost being incurred shall be Rp. 6.700,- per day. So the next calculation result gained maximum production as 74,749 that shall be seaweed production can be increase as Rp. 747,490,- in every one unit production factor addition. And recommended budget is Rp. 7.603.152,-     Keywords : production elasticity, Cobb-Douglas production function, seaweed cultivation.